2020
DOI: 10.1186/s12936-020-03299-1
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic carriage of Plasmodium falciparum by individuals with variant blood groups and haemoglobin genotypes in southern Ghana

Abstract: Background: The ABO and the Rhesus blood group systems, as well as various abnormal haemoglobin (Hb) variants (haemoglobinopathies) are known to influence malaria parasite carriage and disease severity in individuals living in malaria endemic areas. This study identified the blood group and Hb variant distribution and Plasmodium falciparum infection status of afebrile individuals living in southern Ghana. Methods: Afebrile participants were recruited from Obom (358) in the Greater Accra Region and Ewim (100) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…However, there was a trend towards higher rates of asymptomatic infection in blood group O and high rates of symptomatic infection in non-blood group O, which is in line with previous studies in Turkey [ 42 ], China [ 41 ] and the USA [ 43 ], all which found trends but no significant correlations of blood type with disease severity and deaths. Since blood group O prevalence ranges between 47 and 50% [ 44 , 45 ] in Ghana, it is possible that the high cases of mild or asymptomatic COVID-19 individuals in Ghana may be in part attributable to the dominance of blood group O in the population. It has been reported that SARS-CoV-2 receptor-binding domain (RBD) potentially prefers binding to antigen A, expressed on respiratory epithelial cells, than O [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a trend towards higher rates of asymptomatic infection in blood group O and high rates of symptomatic infection in non-blood group O, which is in line with previous studies in Turkey [ 42 ], China [ 41 ] and the USA [ 43 ], all which found trends but no significant correlations of blood type with disease severity and deaths. Since blood group O prevalence ranges between 47 and 50% [ 44 , 45 ] in Ghana, it is possible that the high cases of mild or asymptomatic COVID-19 individuals in Ghana may be in part attributable to the dominance of blood group O in the population. It has been reported that SARS-CoV-2 receptor-binding domain (RBD) potentially prefers binding to antigen A, expressed on respiratory epithelial cells, than O [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obom is a high malaria parasite prevalence setting in the Ga South municipality of Greater Accra Region of Ghana (Fig. 1 ) with a microscopy estimated parasite prevalence of 35% in 2014 [ 5 , 12 ] and 41.8% in 2019 [ 29 ]. Asutsuare is a low malaria parasite prevalence setting in the Shai Osudoku District of the Greater Accra Region of Ghana.…”
Section: Methodsmentioning
confidence: 99%
“…Malaria transmission in Simiw is usually perennial and overlaps with the rainy season peaking in-between May and July. The dry season however begins in November and ends in April ( Acquah et al., 2020 ). Study participants were pupils of the Simiw M/A Basic School-aged from 6 to 12 years.…”
Section: Methodsmentioning
confidence: 99%
“…This study sought to characterize the properties (levels and relative avidities) of naturally-induced antibody responses against two transmission-blocking vaccine candidates, Pfs230 and Pfs48/45 among non-febrile children in southern Ghana. however begins in November and ends in April (Acquah et al, 2020). Study participants were pupils of the Simiw M/A Basic School-aged from 6 to 12 years.…”
Section: Introductionmentioning
confidence: 99%